ANALISIS PEMETAAN KESUKAAN KONSUMEN PADA PRODUK BOLU KEMOJO DI KALANGAN MAHASISWA FAKULTAS PERTANIAN UNIVERSITAS RIAU - Rika Afrianto; Fajar Restuhadi; Yelmira Zalfiatri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this research was to determine the position of the product and the best sponge kemojo attributes from various kinds of sponge kemojo are used, such sponge Kemojo Cik Puan, sponge Kemojo Khadizah, sponge Kemojo Mega Rasa, sponge Kemojo Kembang Sari, sponge Kemojo Insan Sukses, sponge Kemojo Helmi, sponge Kemojo AL-Mahdi. To determine the level of consumer preference to a product. In addition there was still a lack of effort in developing products towards the manufacturer at this time. This research was conducted by mapping methods of internal and external preferences with objects of eight different product types. Sensory analysis used were hedonic and descriptive test. The results of cluster analysis of hedonic test and the main component analysis of the descriptive test were then analyzed by using the preference mapping technique, with the sensory attributes used in sponge kemojo products taste pandanus, sweetness, burning, testeful, green color, aroma of eggs, caramel, tenderness in the mouth, legit, vacancy rate, subtlety of texture. From the results of the analysis conducted, the productssponge sponge Cik Puan products and sponge Kembang Sari most favored by the panelists.Keyword:sponge kemojo, preference mapping.